Racing an ironman triathlon with pneumonia; a case report - Kirill, M. -S.; Danica, B. S.; Al-Shehhi, Galea, D. (Asian Journal of Sports Medicine, 2010)
Background: Athletes present a different category of the population. Trivial complaints may mask more serious illness, especially when the athlete is undergoing intensive training, and the function of his immune system may be sub-optimal. Case Presentation: A triathlete presented a few days after completing an Ironman race, complaining of lethargy, pleuritic chest pain and loss of appetite. On examination he was afebrile, tachycardic and had decreased lower left lung air entry accompanied by crackling. A chest x-ray revealed left-sided basal pneumonia with a para-pneumonic effusion. Blood tests were unremarkable. The athlete was treated with oral antibiotics, and was advised to stop exercise completely for eight weeks. He made a full recovery and completed further Ironman races within a year. Conclusion: The case highlights that clinicians treating elite endurance athletes must exclude severe infection, even when the clinical signs are few or absent. The reason is that if these athletes continue to train, serious complications could ensue due to their compromised resistance to infection.